Lighting the way : toward a sustainable energy future (InterAcademy Council, 2007)
Commissioned by the governments of Brazil and China, this report identifies a scientific consensus framework for directing global energy development. "Lighting the way" establishes the best practices for a global transition to a clean, affordable and sustainable energy supply in both developing and developed countries. The report addresses incentives that can accelerate the development of innovative solutions, provides recommendations for financial investments in research and development and explores other transition pathways that can transform the landscape of energy supply and demand around the globe.